A Note on Gödel-Dummet Logic LC - Robles, Gemma; Méndez, José M. (Bulletin of the Section of Logic, 2021)
Let \(A_0,A_1,...,A_n\) be (possibly) distintict wffs, \(n\) being an odd number equal to or greater than 1. Intuitionistic Propositional Logic IPC plus the axiom \((A_0→ A_1)...(A_n-1→ A_n)(A_n→ A_0)\) is equivalent to Gödel-Dummett logic LC. However, if \(n\) is an even number equal to or greater than 2, IPC plus the said axiom is a sublogic of LC.